Effect of Temperature on the Chemical Characteristics of Vegetable Oils Consumed in Ibadan, Nigeria - Dawodu, Modupe O.; Olutona, Godwin O.; Obimakinde, Samuel O. (Pakistan Journal of Nutrition, 2015)
The effect of changing temperature on various chemical characteristics of vegetable oils sold in Bodija Market, Oyo State, Nigeria was studied. The chemical characteristics were investigated within a temperature range of 25-300°C. The paper also investigated the rate of change of the various chemical parameters with increasing temperature, as suggested by the slope of linear graph of each cooking oil. The peroxide values (6.01-7.02 Meq/kg) were highest in palm kernel oil (PKO), followed by olive oil (OO) (5.20-6.10 Meq/kg) but were lowest in palm oil (PO) (1.80-2.31 Meq/kg). The iodine values were highest (60.0-70.0 g/100 g of sample) in sunflower oil (SFO), followed by soybean oil with values of 58.75-60.0 g/100 g of sample and were lowest (19.2-20.2 g/100 g of sample) in PO. Olive oil (OO) had the highest acid values from 6.01-7.40 mg KOH/g, followed by PKO (3.01-3.99) and the lowest values were recorded for soybean oil (2.80-3.81 mg KOH/g). For the free fatty acid, the highest values (2.49-3.50%) were observed for PO, followed by OO (2.61-3.05%) and the least values were found in SO. The rate of change in PV, as demonstrated by the positive slope ranged from 0.001 Meq/kg/°C in PO to 0.05 Meq/kg/°C in both SO and SFO. The highest rate of change in AV (0.007 mg KOH/g/°C) was obtained for PO, while the lowest value (0.003 mg KOH/g/°C) was recorded for SO, OO and SFO. The rate of change in the free fatty acid value with changing temperature was 0.003, 0.001, 0.002, 0.001 and 0.001%/°C for PO, SO, OO, PKO and SFO oil respectively. However, negative rates were recorded for the iodine values as evidenced by the reduction in the value of this characteristic with increasing temperature. The respective rates of change for PO, SO, OO, PKO and SFO were -0.003, -0.004, -0.013, -0.011 and -0.009 g/100 g of sample/°C. Although our research shows the change in the chemical characteristics with increase in temperature is low, the rate of change must be monitored because of the likely deterioration of the overall quality of the oil at elevated temperatures.